Tidung Language Revitalization through Local-Content Learning in A Multicultural Elementary School in Tarakan, Indonesia - St Saenab; Arina Restian; H. Husamah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
The declining intergenerational use of the Tidung language in multicultural Tarakan has made elementary-school local-content learning an important but underexamined space for language revitalization. This study analyzes how Tidung language learning is implemented as local content in Grade 5 at SDN 028 Tarakan and how policy actors, school stakeholders, families, and customary institutions interact in supporting or constraining revitalization. A descriptive qualitative case-study design was used, with SDN 028 Tarakan selected as a bounded case because it represents an urban multicultural school where Tidung is formally taught although many students do not use it in daily home communication. Data were collected from August to October 2025 through interviews, classroom observations, and document analysis involving 22 informants: one principal, one Grade 5 teacher, twelve Grade 5 students, four parents, two Education Office representatives, and two Tidung customary leaders. The analytical focus was the policy-to-practice translation of Tidung local-content learning, particularly curriculum implementation, teacher readiness, student engagement, material availability, and home/community language support. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, conclusion drawing, and verification. The findings reveal four central themes: strong policy and stakeholder support, teacher-led adaptation under material constraints, positive but mostly receptive student engagement, and an ecosystem gap between school learning and home/community language use. Concrete classroom evidence showed that students were able to repeat greetings, name daily objects, and sing simple Tidung songs, but they rarely initiated spontaneous Tidung dialogue without teacher prompting. Teachers compensated for the lack of standardized books and audio materials by preparing vocabulary sheets, using classroom objects, and adapting songs and short stories. Parents and customary leaders supported the program culturally, but home use remained limited because many families used Indonesian or other ethnic languages in daily interaction. The study proposes a policy-to-practice revitalization model in which local regulation must be followed by standardized materials, systematic teacher training, participatory cultural resources, technology-based media, and family-community language practices. Its novelty lies in showing that, in a multicultural urban setting, school-based local-language revitalization functions first as institutional legitimization and cultural awareness building, but it cannot develop young active speakers unless school exposure is connected with family routines, community validation, and authentic communicative domains.